2020
DOI: 10.1684/epd.2020.1218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electrographic features of persistent seizures and status epilepticus associated with anti‐NMDA receptor encephalitis (anti‐NMDARE)

Abstract: Aims. Based on a multicenter cohort of people with anti‐NMDA receptor encephalitis (anti‐NMDARE), we describe seizure phenotypes, electroencephalographic (EEG) findings, and anti‐seizure treatment strategies. We also investigated whether specific electrographic features are associated with persistent seizures or status epilepticus after acute presentation.Methods. In this retrospective cohort study, we reviewed records of children and adults with anti‐NMDARE between 2010 and 2014 who were included in the Rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Diagnosis of autoimmune encephalitis and demyelinating disorders has become increasingly common in the past decade. [23][24][25][26] Autoimmune disorders alone represent an important etiology of SE, and autoimmune or paraneoplastic SE may be particularly susceptible to progression to refractory SE. 27,28 In this situation, prompt immunomodulating therapies are often required to terminate seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of autoimmune encephalitis and demyelinating disorders has become increasingly common in the past decade. [23][24][25][26] Autoimmune disorders alone represent an important etiology of SE, and autoimmune or paraneoplastic SE may be particularly susceptible to progression to refractory SE. 27,28 In this situation, prompt immunomodulating therapies are often required to terminate seizures.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was revealed that SE patients with symptomatic etiologies were exposed to higher risks of unfavorable functional recovery. Diagnosis of autoimmune encephalitis and demyelinating disorders has become increasingly common in the past decade 23–26 . Autoimmune disorders alone represent an important etiology of SE, and autoimmune or paraneoplastic SE may be particularly susceptible to progression to refractory SE 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, EDB has been associated with longer hospitalization, ICU admission, and poor long-term outcomes [ 14 , 55 , 58 ], while GRDA was strongly associated with abnormal movements [ 56 ] and treatment-response to second-line therapies [ 59 ]. In contrast, EEG findings in long-term monitoring during the acute phase of the disease have not been found to predict the persistence of seizures in long-term follow up [ 60 ].…”
Section: Clinical and Paraclinical Features As Markers Of Anti-nmdar Encephalitismentioning
confidence: 99%